2004
DOI: 10.1016/s0014-5793(03)01523-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of sphingosylphosphocholine by neutral sphingomyelinases

Abstract: Sphingosylphosphocholine (SPC), the N-deacylated form of sphingomyelin (SM), is a naturally occurring lipid mediator. However, little is known about the metabolism of SPC. We here report an in vitro assay system for SPC-phospholipase C (PLC). Using this assay system, we demonstrated that nSMase1 and nSMase2, human neutral sphingomyelinases (SMases), are capable of hydrolyzing SPC e⁄ciently under detergent-free conditions. Bacterial and plasmodial neutral SMases also showed SPC-PLC activity. The substrate speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Recently, the enzyme activities of nSMase 1 and nSMase 2 toward several phospholipids have been reported. 24) These two nSMases hydrolyzed SM more predominantly than lysoPAF in the presence of Triton X-100 and phosphatidylserine. We found that the hydrolysis of lysoPAF catalyzed by B. cereus SMase was restrained to the same extent as that of lysoPC in the presence of Triton X-100 (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…Recently, the enzyme activities of nSMase 1 and nSMase 2 toward several phospholipids have been reported. 24) These two nSMases hydrolyzed SM more predominantly than lysoPAF in the presence of Triton X-100 and phosphatidylserine. We found that the hydrolysis of lysoPAF catalyzed by B. cereus SMase was restrained to the same extent as that of lysoPC in the presence of Triton X-100 (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…The fifth largest increase was observed for sphingomyelin phosphodiesterase 3 neutral (Smpd3), which is a member of a large superfamily of magnesium-dependent phosphohydrolases. Smpd3 is an enzyme which hydrolyzes sphingosylphosphocholine in the plasma membrane to produce ceramide (Marchesini et al, 2003;Miura et al, 2004). It was originally identified as a brainspecific neutral sphingomylelinase (Hofmann et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Neutral SMasess are ubiquitously expressed but are expressed at higher levels in the brain and in the embryonic bone growth plate (21). The phenotype of smpd3 −/− mice mimics that of human chondrodysplasia, which manifests as a genetic disorder with clinical heterogeneity (2,12).…”
Section: Discussionmentioning
confidence: 99%